Abundance of benthic fauna of a post harvest rice field in Bangladesh Agricultural University Campus, Mymensingh (University Journal of Zoology, Rajshahi University, 2007)
Key words: Benthos; post harvest rice field Univ. j. zool. Rajshahi Univ. Vol.22, 2003. pp. 105-110